A courtyard in a courtyard - Yiyang Li 1997- (2024)
Sandgerði is a vibrant town near Iceland’s international airport known for its fishing industry. The site situated on a critical point between the old town and the new inhabitant area introduces a new residential model. It features a modern pitched house with a small courtyard designed to meet the needs of diverse family generations, including a welcoming space for an international family new to Iceland, facilitating their social integration. This development revitalizes the street with full street corner elevation and includes a secluded garden that serves as a communal leisure space for neighbours, fostering community interaction and enhancing the social fabric of Sandgerði.